Synthesis & analysis of mechanical and tribological behaviour of silicon carbide and graphite reinforced aluminium alloy hybrid composites. (2020) - kumar, Ashish; Rana, R.S.; Purohit, Rajesh
Abstract: This article mainly focuses on development, characterization and tribological performance of aluminium alloy matrix based hybrid composite strengthening with silicon carbide and Graphite particles. The investigation is carry forward step by step starts with development of hybrid composite, study all the properties to insure its utility in automobile sector possible specially for cylinder blocks, pistons etc. All these are the areas where sliding wear plays a predominant role. Hence Investigation has been done on sliding wear characteristics of this composite developed by mechanical agitation casting route i.e. aluminium alloy strengthened by 3 wt% and 6 wt% of silicon carbide addition with constant 2 wt% graphite particles. To evaluate each and every parameter the test was performed at two sliding distances of 1256.56 m and 2513.27 m at sliding velocities 1.047 m/s and 2.094 m/s under three loading conditions i.e. 10 N, 30 N, and 50 N. All these tests were performed for 3 compositions of the Hybrid composite. Results clearly shows wear resistance obtained at maximum (6 wt%) silicon carbide with constant graphite. Mechanical tests along with characterization of composite are to be investigated. Maximum tensile strength 234.57 MPa and hardness 49.5 BHN noticed in 6 wt% SiC at constant Gr reinforced composite. Microstructure reveals the grain refinement with graphite particles addition and overall hardness of composite improves with up gradation of SiC weight percentage.